Hannah's hero eaudiobook - Dixon, Ruby (Icehome, 2020)
All I want is Hannah. We've resonated, but she avoids me. She has made it very clear that she wants no mate, whether he has two arms or four. But when others leave the Icehome beach camp for a getaway to a fruit-filled cave, Hannah wants to go, and she needs a companion. Me. For the first time, we talk . . . and I realize my female isn't as good at ignoring me as she thinks. She watches me with hungry eyes. She blushes at my bold words. When I touch her? She no longer runs away. It is time I show her that a Strong Arm hunter can be the right mate for her, and that four arms can hold her twice as closely as two.